Cultural Trauma, Prophetic Discourse and the Sack of Rome in 1527 - van den Oever, Joost (Journal of religion in Europe, 2015)
The aim of this article is to shed new light on the relationship between catastrophic historical events, cultural trauma and prophetic discourse, by making use of both historical and sociological analytical models. For this purpose, an exemplary case study has been found in the horrible and devastating sack of Rome in 1527. The destruction of Rome had been prophesied countless times, and in 1527 these prophecies seemed to have come true. How, then, did the prophetic discourse influence the ways in which the traumatic violence and breakdown of social order were perceived, experienced and remembered by various contemporaries? To answer this question, combining historical and sociological models in an original way, I will argue that trauma can—with great reward—be studied as a cultural construct, in which prophetic discourse can be interpreted as a template for framing the traumatic experience into a narrative.